Implikacje polityki rozszerzania NATO - Zięba, Ryszard (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2023)
Celem tego artykułu jest ukazanie z perspektywy neorealizmu implikacji pozimnowojennego rozszerzenia NATO. Implikacje te należy widzieć na wielu poziomach: (a) bezpieczeństwa nowych członków Sojuszu Północnoatlantyckiego, (b) USA i spoistości NATO, (c) Rosji, (d) militaryzacji stosunków w Europie, (e) wybuchu wojny między Rosją a Ukrainą, oraz (f) globalnego systemu międzynarodowego. Wojna na Ukrainie – będąca efektem m.in. polityki rozszerzania NATO – jest wojną zastępczą Rosji z NATO o konsekwencjach globalnych, które przyspieszają rekonfigurację całego ładu międzynarodowego. The aim of this paper is to present the implications of post-Cold War NATO enlargement from the perspective of neorealism. These implications should be seen on many levels: (a) the security of the new members of the North Atlantic Alliance, (b) the USA and NATO cohesion, (c) Russia, (d) the militarization of relations in Europe, (e) the outbreak of war between Russia and Ukraine, and (f) the global international system. The war in Ukraine – resulting from, among others, NATO’s expansion policy – is a proxy war between Russia and NATO with global consequences that accelerate the reconfiguration of the entire international order.
Implications of NATO enlargement policy
Keywords: NATO; Europa; USA; Rosja; wojna na Ukrainie; globalny system międzynarodowy; Europe; Russia; war in Ukraine; global international system